Postoperative complications and predictors of mortality in surgery for left-sided infective endocarditis: a single-center retrospective study - S. T. Enginoev; V. V. Demetskaya; D. Yu. Kozmin; V. V. Pasyuga; D. A. Demin; E. V. Demina; D. R. Stompel; I. I. Chernov (Российский кардиологический журнал, 2023)
Aim. To assess postoperative complications and predictors of mortality in surgery for left-sided infective endocarditis (IE).Material and methods. The retrospective analysis included 222 cases of IE in 216 patients who were operated on from January 2015 to November 2022. Inclusion criteria: age of patients ≥18 years, definite or probable (Duke criteria) left-sided IE of aortic and/or mitral valves. There were following exclusion criteria: isolated right-sided IE (tricuspid valve, pacemaker endocarditis), nonbacterial thrombotic endocarditis and chronic IE. Endpoints: inhospital mortality, postoperative complications (delirium; perioperative stroke; resternotomy for bleeding; perioperative myocardial infarction; acute heart failure requiring extracorporeal membrane oxygenation or intra-aortic balloon pumping; respiratory failure requiring tracheostomy; acute kidney injury requiring renal replacement therapy; conduction disorder requiring pacemaker implantation).Results. Median age was 53 [38,0; 61,0] years, while the majority of patients were men (73,9%). Inhospital mortality was 8,6%. The most common postoperative complications were delirium (19,8%) and bleeding requiring resternotomy (10,4%). The incidence of perioperative stroke was 2,3%, perioperative myocardial infarction - 0,9%, respiratory failure with tracheostomy – 4,5%, pacemaker implantation – 2,7%, renal replacement therapy – 6,8%. According to multivari ate analysis, Predictors of inhospital mortality were creatinine clearance level (odds ratio (OR), 0,976; 95% confidence interval (CI): 0,956-0,996; p=0,020), time of cardiopulmonary bypass (OR, 1,014; 95% CI: 1,006-1,021 , p<0,001), deli rium (OR, 7,058; 95% CI: 1,824-27,330, p=0,005) and acute kidney injury requiring renal replacement therapy (OR, 28,620; 95% CI: 6,508-125,964; p<0,001).Conclusion. Surgical treatment of left-sided IE has satisfactory inho spital outcomes. The study identified simple clinical factors (creatinine clearance, cardiopulmonary bypass time, delirium, acute kidney injury) associated with inhospital mortality.